Treatment preferences for biologicals in psoriasis: experienced patients appreciate sustainability - Kromer, Christian; Ludwig-Peitsch, Wiebke; Herr, Raphael; Schmieder, Astrid; Sonntag, Diana; Schaarschmidt, Marthe-Lisa (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Background and objectives: Treatment satisfaction can be improved by integrating patients’ preferences into shared decision-making. We recently investigated patients’ preferences for attributes of biologicals, and showed high preferences for safety and efficacy. The objective of the present study was to assess the impact of treatment experience on these preferences. Patients and methods: Preferences for outcome (probability of 50 % and 90 % improvement, time until response, sustainability of success, probability of mild and severe adverse events, probability of ACR 20 response) and process attributes (treatment location, frequency, duration, and delivery method) were analyzed in 200 participants with moderate-to-severe psoriasis using conjoint analysis. The impact of current and previous therapies, disease duration, and treatment satisfaction on ‘Relative Importance Scores’ was determined by analysis of variance, post hoc tests, and multivariate regression. Results: Participants presently on topical therapy (p = 0.02) or phototherapy (p = 0.032) placed more importance on treatment duration than others. Individuals who had previously been given traditional systemic agents (p = 0.028) or biologicals (p = 0.044) favored sustainability more than others. With an increasing number of systemic agents ever received (p = 0.045) and longer disease duration (p = 0.018), the latter attribute became increasingly important. Conclusions: Patients’ preferences for biologicals vary in correlation with treatment experience and disease duration, aspects to be addressed in the context of shared decision-making.
Gesehen am 12.07.2017